OPPORTUNITIES OF CENTRAL ASIAN STATES IN THE SYSTEM OF INTERNATIONAL GEOPOLITICAL RELATIONS - Jumaniyozov Xushnud Sapayevich (Scholar Express Journal, 2022)
This article describes the natural-geographical, socio-economic, logistical capabilities of the Central Asian states. Studies on the concept of Central Asia, its territory and territory are analyzed. The natural and geographical environment, socio-economic development and logistics opportunities of the countries in the region are considered. In the analysis of the processes in the region, the methods of analysis and synthesis, historical and logical, comparative comparison, generalization were used
Keywords: Central Asia; Central Asia the Great Silk Road; geography; logistics